Sikarju: Expert System of Major Recommendation to Increase the Chances of Being Accepted by University - Siti Izati Nabila; Ami Anggraini Samudra; Irsyadunas Irsyadunas (Department of Informatics Engineering, Universitas Muhammadiyah Purwokerto, 2023)
Major is one of the important factors in the world of lectures. Along with the increasing need for knowledge and skills required in the world of work, increasing the number of majors offered by tertiary institutions. The number of considerations from prospective students regarding the selection of majors causes students to be confused in determining the best major they will choose to continue their education. The research aims to design an expert system-based website that will be used to provide major recommendations. The method to be used is the forward chaining method, where this method works by matching data based on predetermined facts, then obtaining results based on matching the data. Based on the black box testing that has been done, the results show that the designed expert system is by the expected functionality. Therefore this expert system can be said to be feasible to use.